Beethoven's conversation books. - Beethoven, Ludwig van, 1770-1827 (The Boydell Press, 2019)
A complete new edition of Beethoven's conversation books, now translated into English in their entirety for the first time. Covering a period associated with the revolutionary style of what we call "late Beethoven."